Case Report: Severe Side Effects Following Treatment With First Generation Antipsychotics While Cariprazine Leads to Full Recovery - Taube, Maris (Frontiers in Psychiatry, 2021)
Schizophrenia is a psychiatric disorder characterized by positive, negative and cognitive symptoms. Patient’s cooperation with health care professionals, compliance with the treatment regime and regular use of medications is one of the preconditions for a favorable course of disease. Negative experience following the use of a first-generation antipsychotic to treat first-episode psychosis poses serious challenges for the patient’s motivation for further medication use. The choice of cariprazine in the given clinical case restored the patient’s faith in therapy and facilitated cooperation with the physician ensuring effective control of negative and positive symptoms and good functioning for a period of one year already. Cariprazine could be a good option for maintenance therapy following first-episode psychosis, especially in situations when a patient has a negative first experience associated with the use of antipsychotics.